Efficient lamellar two‐dimensional proton channels derived from dipole interactions in a polyelectrolyte membrane. Issue 8 (30th April 2022) - Yu, Weisheng; Zhang, Kaiyu; Zhang, Jianjun; Liang, Xian; Ge, Xiaolin; Ge, Zijuan; Wei, Chengpeng; Song, Wanjie; Xu, Tongwen; Wu, Liang
Abstract: Precise control over the micromorphology of polyelectrolytes is the primary step toward understanding the structure–morphology–property relationships, ultimately determining the mass transfer characteristics. We report a novel polyolefin‐scaffolded proton‐exchange membrane (PEM) with the sectional installation of dipole–dipole interactions for this task. Experimental and theoretical investigations demonstrate that such noncovalent interactions drive the desired aggregation of ionic chains to form the hydrated two‐dimensional (2D) ionic nanochannels. Micromorphology studies visualize the resultant lamellar topological morphology consisting of orderly arranged hydrophilic ionic and nonionic nanophases. The resulting membrane exhibits excellent proton conductivity (176–273 mS cm −1 at the temperature ranges from 30°C to 80°C) and H2 /O2 fuel cell performance (especially at the lower relative humidity, the maximum power density is doubled that of commercial Nafion 212 at 40% relative humidity). Overall, we developed a promising design of the polyelectrolyte microstructure precise regulation for efficient ion conduction.